2007
DOI: 10.1136/bmj.39100.417072.be
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-governmental organisations in physician assisted suicide

Abstract: Could right to die organisations be part of the solution to the many ethical difficulties doctors face over assisted suicide? Stephen Ziegler and Georg Bosshard examine how two organisations in Switzerland and Oregon help people die

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 9 publications
0
43
0
2
Order By: Relevance
“…The organization offers information, support, and attendance at the death of clients who qualify for the ODDA. 6,7 In 2005, Compassion and Choices reported that they had given information to or assisted 180 of the 246 (73%) persons who died of PAD under Oregon's law. 6 The two medical centers kept a centralized registry of patients who explicitly requested a lethal prescription from a physician to assure compliance with the law.…”
Section: Methodsmentioning
confidence: 99%
“…The organization offers information, support, and attendance at the death of clients who qualify for the ODDA. 6,7 In 2005, Compassion and Choices reported that they had given information to or assisted 180 of the 246 (73%) persons who died of PAD under Oregon's law. 6 The two medical centers kept a centralized registry of patients who explicitly requested a lethal prescription from a physician to assure compliance with the law.…”
Section: Methodsmentioning
confidence: 99%
“…74 Volunteers of the right to die organisations provide support to the individual who dies and manage complications. 75 It has been suggested that it may be preferable to have volunteer assistance during the final act insofar as the assistance of Ôa nurse with special training and experience in this field [may be preferable to that of] a general practitioner who has no particular training and has never engaged in assisted suicide beforeÕ. 76 Dignitas, a Swiss Ôright to dieÕ organisation, has recently assisted a number of suicides by means of oxygen deprivation with helium.…”
Section: Due Medical Carementioning
confidence: 99%
“…EDS volunteers are trained in counselling, and may refer individuals not meeting the criteria for assisted suicide to counselling. 324 In acute care hospitals, a psychiatric assessment may be provided if indicated. 325 Should Ôtreatment adaptationÕ be possible, this would appear to rule out the possibility of assisted suicide, although it is not clear whether a refusal of treatment will also rule out assisted suicide.…”
Section: Consultation and Referralmentioning
confidence: 99%
“…De facto, a 1997 attempt to decriminalise euthanasia failed. The article does not require the involvement of a physician nor that the patient is terminally ill. Switzerland permits anyone to assist in another's death regardless whether the candidate is terminally ill or not (Ziegler & Bosshard, 2007). The Swiss Academy of Medical Sciences states that assistance in dying is "not part of a physician's activity".…”
Section: Euthanasia's Historical Backgroundmentioning
confidence: 99%